2019
DOI: 10.2139/ssrn.3766934
|View full text |Cite
|
Sign up to set email alerts
|

Shareholders and Stakeholders around the World: The Role of Values, Culture, and Law in Directors’ Decisions

Abstract: We present evidence on the way personal and institutional factors could together guide public company directors in decision-making concerning shareholders and stakeholders. In a sample comprising more than nine hundred directors originating from over fifty countries and serving in firms from twenty three countries, we confirm that directors around the world hold a principled, quasi-ideological stance towards shareholders and stakeholders, called shareholderism, on which they vary in line with their personal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 148 publications
(129 reference statements)
0
8
1
Order By: Relevance
“…Thus, for boards to make effective CSR investments, it is important to have directors with backgrounds that value CSR and have sufficient knowledge and means to integrate it into the heart of the firm's activities. Adams and Licht [12] studied the role of directors' cultural background and legal origins in their decision-making regarding shareholders and stakeholders. Using a survey-based quasi-experimental approach, they found that legal regulations with strong creditor protection and cultural norms that emphasize on egalitarianism and harmony shape directors to be stakeholder-oriented.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for boards to make effective CSR investments, it is important to have directors with backgrounds that value CSR and have sufficient knowledge and means to integrate it into the heart of the firm's activities. Adams and Licht [12] studied the role of directors' cultural background and legal origins in their decision-making regarding shareholders and stakeholders. Using a survey-based quasi-experimental approach, they found that legal regulations with strong creditor protection and cultural norms that emphasize on egalitarianism and harmony shape directors to be stakeholder-oriented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, we focus on a specific type of outside directors-affiliated banker directors-and attempt to understand whether and to what extent affiliated bankers on board influence firms' CSR investments. Adams and Licht [12] show that cultural backgrounds and legal origins guide directors in decision-making regarding stakeholders and shareholders. Moreover, as researchers show that directors rely on their skills, such as experiences [13,14] to fulfill their roles, it is plausible that directors' banking backgrounds play an important role in firms' CSR investments.…”
Section: Introductionmentioning
confidence: 99%
“…Second, by showing that highly stakeholder-orientated directors are more prone to opinion conformity than directors with a low stakeholder-orientation, we underpin the importance of stakeholder-orientation as a director attitude. We show that it not only affects directors' individual decision-making (Adams and Licht, 2019;Adams et al, 2011), but also how stakeholder-oriented directors react to conformity pressure, thus to group-level dynamics. This finding resonates with general strategic management research showing significant firm-level challenges associated with adopting a stakeholder-orientation (Bettinazzi and Zollo, 2022;Garcia-Castro and Francoeur, 2016).…”
Section: Company Descriptionmentioning
confidence: 90%
“…Many boards publicly commit themselves to serve the interests of all parties affected by their strategies (e.g., Business-Roundtable, 2019) and recognize directors' attitude towards stakeholders as perhaps the most important prerequisite for a well-functioning stakeholder model (de Brauw, 2020). This arguably makes it appealing to appoint stakeholder-oriented directors to boards (i.e., directors with a proclivity to take a stance for the needs of various stakeholder groups) in order to ensure that a board maintains this focus in carrying out its board duties (Adams and Licht, 2019;Bebchuk and Tallarita, 2020;Tomlinson et al, 2020). A demand for directors with this attitude is for example visible in investment firms requesting a track record indicating that directors of their investee firms focus on social and environmental aspects (AXA IM, 2022).…”
Section: Company Descriptionmentioning
confidence: 99%
See 1 more Smart Citation